An Experimental Study on Fluoride Removal from Aqueous Solution by Using Thermally Treated Annona Squamosa with and without Presence of the Inert Gas as Adsorbent - Chinthayyanaidu Rudram; L. Partha Praveen; P. Dinesh Sankar Reddy (Novel Aspects on Chemistry and Biochemistry Vol. 2, 2023)
The purpose of this study is to investigate the effectiveness of Pyrolyzed leaves of Custard Apple at 800oC (OPA) in air and in the presence of inert gas (IGPA) as adsorbent materials for removing fluoride from aqueous solutions. The study examines the impact of various parameters, such as particle size, agitation speed, pH, contact time, adsorbent dosage, initial fluoride concentration, and temperature on the adsorption of fluoride onto Annona squamosa. The results indicate that the highest fluoride removal efficiency was achieved at a pH of 7, a contact period of 30 minutes, an agitation speed of 500 rpm, and an adsorbent dosage of 1.5g per 50 mL of fluoride water. The OPA and IGPA achieved fluoride removal efficiencies of 93% and 96%, respectively. The adsorption isotherm modeling studies revealed that the adsorption onto OPA followed the Dubinin-Raudskevitch isotherm model, while IGPA followed the Langmuir isotherm model. The thermodynamic parameters showed that the reaction is endothermic. The kinetics study revealed that the Pseudo second order model best fit both OPA and IGPA. The SEM, FTIR, and XRD patterns of the adsorbent were analyzed to gain a better understanding of the adsorption mechanism. Overall, the study demonstrates the potential of OPA and IGPA as effective adsorbents for removing fluoride from aqueous solutions.